Kajian Kebenaran Sedekah Sebagai Investasi Terbaik Dunia Dan Akhirat - Siti Miftachul; Harnum Nabela; Muhammad Reza; Trendi Firmansyah; Khorina Widya; Siti Uli Nihayati; Ainunnisa Lita; Desmita Nindya; Nur Rofiq (STIKes Ibnu Sina Ajibarang, 2024)
Almsgiving is a form of worship in Islam which has many benefits, not only limited to giving material things, but includes all forms of kindness done sincerely. Alms and infaq have almost the same meaning, namely the activity of giving something to other people or institutions sincerely and hoping for Allah's blessing. In Java there is a tradition called earth charity. The aim of this research was to determine the law of earth almsgiving. Then the role of alms content in the digital era. The method used in this research is library research. This type of normative research examines various internet sources. The results of the research carried out explain that earth almsgiving is in accordance with the teachings of the Islamic religion which encourages its followers to give alms and be grateful for the blessings given by Allah SWT, then people who give alms while creating social media content cannot be punished, and have a positive impact on improving the economy and a sense of caring. towards local UMKM. It is proven that alms is an investment in this world and the hereafter.